Accelerator, Theory of the Firm and the Business Cycle - Tsiang, S. C. (Quarterly Journal of Economics, 1951)
I. Accelerator: an exogenous parameter or an endogenous variable, 325. — II. The unreasonableness of the assumption of a constant accelerator in the light of the theory of the firm, 327. — III. The inelastic supply of capital to individual firms checks the operation of the acceleration principle and tends to make the rate of investment a function of the level of income rather than a function of the rate of change of income during the upswing, 331. — IV. Accelerator and the time dimension of investment, 335. — V. Significance of time dimension of investment in the explanation of the appearance of excess capacity and downturn, 339.